The Unexamined Orwell - Rodden, John (Book collections on Project MUSE., 2011)
In this book the author delves into dimensions of Orwell's life and legacy that have escaped the critical glare, the largely unattended (and even unimagined) Orwell. Rodden discusses how several leading American intellectuals have earned (and often cultivated) the title of Orwell's "successor," including Lionel Trilling, Dwight Macdonald, Irving Howe, Christopher Hitchens, and John Lukacs. The book then turns to Germany, where Orwell - and especially "Orwell"--Is a notable presence, and focuses on the role and relevance of Nineteen Eighty-Four in the now-defunct communist nation of East Germany. Rodden also addresses myths that have grown up around Orwell's life, including his "more than half-legendary" encounter with Ernest Hemingway in liberated Paris in March 1945, and analyzes literary issues such as Orwell's utopian sensibility and his prose style, which are topics that have drawn scant critical attention. Finally, Rodden poses the wistful, endlessly debated question, "W.W.G.O.D.?" (what would George Orwell do?) Moving through the decades since Orwell's death, Rodden speculates about how the prophet of Nineteen Eighty-Four would have reacted to world events. In so doing, Rodden shows how our responses to this question reveal much about our culture's ongoing need to reappropriate "Orwell" and about our own drives and aspirations.--From dust jacket back cover